Bird Migration at the Edge – Geographic and Anthropogenic Factors but Not Habitat Properties Drive Season-Specific Spatial Stopover Distributions Near Wide Ecological Barriers - Schekler, Inbal; Smolinsky, Jaclyn A.; Troupin, David; Buler, Jeffrey J.; Sapir, Nir (Frontiers in Ecology and Evolution, 2022)
Stopping-over is critical for migrating birds. Yet, our knowledge of bird stopover distributions and their mechanisms near wide ecological barriers is limited. Using low elevation scans of three weather radars covering 81,343 km2, we quantified large-scale bird departure patterns during spring and autumn (2014-2018) in between two major ecological barriers, the Sahara Desert and Mediterranean Sea. Boosted Regression Tree models revealed that bird distributions differed between the seasons, with higher densities in the desert and its edge, as well as inland from the sea, during spring and a predominantly coastal distribution in the autumn. Bird distributions were primarily associated with broad-scale geographic and anthropogenic factors rather than individual fine-scale habitat types. Notably, artificial light at night strongly correlated with high densities of migrants, especially in the autumn. Autumn migrants also selected sites located close to water sources. Our findings substantially advance the understanding of bird migration ecology near ecological barriers and facilitate informed conservation efforts in a highly populated region by identifying a few high-priority stopover areas of migrating birds.